THE PROBLEM OF AGGRAVATION OF EPILEPTIC SEIZURES DURING THERAPY WITH ANTIEPILEPTIC DRUGS - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии, 2015)
The paper gives a brief literature review coming to the attention of practitioners to the problem of aggravation in epilepsy. Despite the fact that the purpose of use of antiepileptic drugs is to stop seizures and to suppress epileptic activity on electroencephalogram; in some cases their administration may worsen epilepsy, namely may make seizures more frequent and severer (may cause aggravation). Status epilepticus is the severest manifestation of aggravation. The drugs differ in the risk of aggravation, which also depends on the type of seizures and patient age.